Partisipasi Masyarakat terhadap Pelestarian Hutan Lereng Merapi Melalui Program Agroforestri Kopi di Desa Tlogolele Kecamatan Selo - Fitria, Amalia; Banowati, Eva (Edu Geography, 2018)
Forest destruction of Merapi’s slope caused by fire of volcanic’s eruption and excessive deforesration.This research intend to knowing community activities in a effort to minimize deforestation, extent ofcommunity participation towards forest conservation through the coffee agroforesty and the influenceof community participation on the coffe agroforesty program in Tlogolele Village , Selo Subdistrict.Data collection methods in study are Questionnaire method, observation, interview anddocummentation. Data analysis techniques use to Descriptive, descriptive statistics and simple linearregression. Low community participation is caused by a long coffee harvest period of up to two yearsso the results cannot be directly enjoyed. The results of simple linear regression analysis Y = 9.040 Kerusakan hutan lereng Merapi disebabkan oleh kebakaran letusan gunung merapi danpenebangan hutan secara berlebihan. Penelitian ini bertujuan untuk mengetahui kegiatanmasyarakat dalam upaya meminimalisir kerusakan hutan, tingkat partisipasi masyarakatterhadap pelestarian hutan melalui program Agroforestri kopi, dan pengaruh partisipasimasyarakat terhadap program Agroforestri kopi di Desa Tlogolele Kecamatan Selo.Metode pengumpulan data pada penelitian ini yaitu metode angket, observasi,wawancara, dan dokumentasi. Teknik analisis data menggunakan analisis deskriptif,statistik deskriptif, dan regresi linier sederhana. Rendahnya partisipasi masyarakatdisebabkan oleh masa waktu panen kopi yang lama hingga dua tahun sehingga hasilnyatidak bisa langsung dinikmati. Hasil analisis regresi linier sederhana Y= 9,040 + 0,791 Xmenunjukkan hubungan yang bersifat positif, artinya semakin tinggi partisipasimasyarakat maka akan semakin tinggi pula keberhasilan program Agroforestri kopi.+ 0.791 X indicate a positive relationship, meaning that the higher the community participation,the higher the success of the coffee agroforestry program. Tlogolele Village community participationis low. The number of coffee plant seeds that have not been moved into the forest is a benchmark forthe lack of success of the coffee agroforestry program. This was influenced by the low participation ofthe Tlogomulyo Hamlet community who were not active during the program implementation.